1990
DOI: 10.3382/ps.0691731
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Restrictive and Compensatory Growth on the Incidence of Leg Abnormalities and Performance of Commercial Male Turkeys

Abstract: To determine if excessive body weight and dietary protein and amino acid intake contribute to the incidence of leg deformities, the growth of male turkeys was restricted from 6 to 12 wk and from 6 to 20 wk of age by feeding diets for ad libitum intake that were low in dietary protein and amino acids (74% of controls). For those turkeys whose growth was restricted from 6 to 12 wk of age, a return to control diets (low compensatory plane) or to 20% above control diets (high compensatory plane) with respect to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
22
1

Year Published

1990
1990
2003
2003

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 18 publications
3
22
1
Order By: Relevance
“…Recent studies conducted in Switzerland have reported a similar TD incidence to that reported in the present experiment (Reinmann et al, 1995). Some earlier studies have shown a lower prevalence: Poulos (1978) reported an incidence of 51% in non-lame and 86% in lame turkeys and a range from 10 to 30% was reported in a number of experiments (Hester et al, 1983(Hester et al, , 1990Ferket and Sell, 1989;Hester and Ferket, 1998). Walser et al (1982) reported an overall prevalence of 79% in 5 lines of turkeys that weighed about two-thirds of the line used in this experiment.…”
Section: Discussionmentioning
confidence: 89%
“…Recent studies conducted in Switzerland have reported a similar TD incidence to that reported in the present experiment (Reinmann et al, 1995). Some earlier studies have shown a lower prevalence: Poulos (1978) reported an incidence of 51% in non-lame and 86% in lame turkeys and a range from 10 to 30% was reported in a number of experiments (Hester et al, 1983(Hester et al, , 1990Ferket and Sell, 1989;Hester and Ferket, 1998). Walser et al (1982) reported an overall prevalence of 79% in 5 lines of turkeys that weighed about two-thirds of the line used in this experiment.…”
Section: Discussionmentioning
confidence: 89%
“…Food restriction has been used as an alternative management procedure to reduce the overall incidence of leg abnormalities in broiler chickens (Ferket and Sell, 1989a;Hester et al, 1990;Robinson et al 1992;Kirn and Firman, 1993). However, food restriction could change long bone characteristics over the growing period of broiler chickens.…”
Section: Discussionmentioning
confidence: 99%
“…One of these procedures involves early food restriction, with subsequent compensatory growth allowing the birds to reach the heavy market weights needed for deboning (Lilburn, 1994). Several studies carried out to investigate the impact of nutrient restriction on leg abnormalities have concluded that the reduction in leg problems was probably associated with lower body weight or increased activity in birds at a critical stage in leg bone development (Ferket and Sell, 1989a,b;Hester et al, 1990). Other workers have reported that longterm or short-term protein restriction affects linear or appositional bone growth in different ways (Hurwitz et al, 1992;Turner and Lilburn, 1992).…”
Section: Introductionmentioning
confidence: 98%
“…Specifically, dietary protein levels of 60, 70, or 80% of the National Research Council's (NRC, 1984) recommended levels did not result in compensatory growth (Ferket and Sell, 1989a), and carcass quality and yield were unaffected with the exception of the 60% protein diet in which breast muscle was decreased (Ferket and Sell, 1989b). Hester et al (1990) reported that feeding a large strain of male turkeys a diet low in protein and AA (74% of controls) from 6 to 12 wk of age, with a return to control rations from 12 to 20 wk of age, resulted in compensatory growm by market age of 20 wk. Advantages of feeding this low compensatory plane diet, as compared with feeding the control diet, included a lower incidence (P<.06) of leg abnormalities (mainly valgusvarus deformities) and improved protein to weight gain ratios which should lead to lower feed cost (Hester et al, 1990).…”
Section: Introductionmentioning
confidence: 98%